Evaluation of Serum Copper Level in Acne Vulgaris Patients - الشاعر ريم; محمد عماد خياط; جمال خدام (Latakia University Journal -Medical Sciences Series, 2023)
Background: Detection of low serum copper in patients with acne vulgaris leads to considering it as a good treatment option due to its low price, effectiveness, and lack of side effects, and it may reduce the use of other treatments with multiple side effects. Objectives: the main objective: Evaluation of the level of serum copper in patients with acne vulgaris and its comparison with the level of healthy people. Secondary objective: Studying the relationship between the level of copper in the serum, the severity, duration of acne and the sex of the patient. Materials and methods: Statistical study (case - control) The research sample included 62 patients with acne vulgaris who attended the Dermatology and Sexually Transmitted Diseases Clinic at Tishreen University Hospital in Lattakia during the time period 2021-2022 and met the inclusion criteria in the research. As for the control sample, it included 37 patients who visited the dermatological clinic for reasons other than acne vulgaris. The diagnosis of acne vulgaris was made clinically. The severity of acne was determined for each patient using the Global Acne Grading System (GAGS). Serum copper was also measured in the central laboratory at Tishreen University Hospital using a semi-automatic HUMAN device, using the colorimetric test method. Results: The value of serum copper decreases in patients with acne vulgaris compared to healthy persons, and it also decreases with increasing duration of infection with acne and with increasing severity. While there is no relationship between the value of serum copper and the sex of the patient. Conclusion: Serum copper analysis should be performed routinely for patients with acne vulgaris and based on its result oral copper supplementation should be given to patients to improve treatment outcomes.